2015
DOI: 10.1175/mwr-d-15-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Strongly Coupled Ocean–Atmosphere Data Assimilation with an Interface Solver

Abstract: In a strongly coupled data assimilation (DA), a cross-fluid covariance is specified that allows measurements from a coupled fluid (e.g., atmosphere) to directly impact analysis increments in a target fluid (e.g., ocean). The exhaustive solution to this coupled DA problem calls for a covariance where all available measurements can influence all grid points in all fluids. Solution of such a large algebraic problem is computationally expensive, often calls for a substantial rewrite of existing fluid-specific DA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 32 publications
1
83
0
Order By: Relevance
“…For our model, the atmosphere ensemble error correlation length scales are approximately 2 orders of magnitude greater than those for the ocean over the time scales we consider; to ensure that the atmospheric variables do not have undue influence on the ocean beyond the near-surface boundary, we need to account for this disparity when we define the localization length scales for the subblock AO . Similarly to Frolov et al (2016), we found that this could be achieved by replacing (3) with the scaled distancê …”
Section: Aamentioning
confidence: 81%
See 4 more Smart Citations
“…For our model, the atmosphere ensemble error correlation length scales are approximately 2 orders of magnitude greater than those for the ocean over the time scales we consider; to ensure that the atmospheric variables do not have undue influence on the ocean beyond the near-surface boundary, we need to account for this disparity when we define the localization length scales for the subblock AO . Similarly to Frolov et al (2016), we found that this could be achieved by replacing (3) with the scaled distancê …”
Section: Aamentioning
confidence: 81%
“…The first method is based on forming a multivariate localization matrix from the univariate GC function. A similar approach is adopted by Frolov et al (2016) for localizing the coupled cross-domain ensemble covariances in their atmosphere-ocean interface solver. One potential flaw in this approach, noted by Roh et al (2015), is that a multivariate localization matrix constructed this way is not guaranteed to be positive definite; they propose fixing this by setting equal to the product of a univariate function and a symmetric, positive-definite matrix whose diagonal entries are one.…”
Section: Localizationmentioning
confidence: 99%
See 3 more Smart Citations